Analisis Pengaruh Kinerja Keuangan Terhadap Keputusan Investasi Perusahaan - Veronika Christine Mevelia; Thesalonika Djumaifin; Achmad Bagas Djuan Rajendra; Felix Chandra Pranoto; Lisrotul Munawaroh; Ardhi Islamudin (Jurnal Manajemen Bisnis Era Digital, 2024)
This research aims to examine the impact of financial performance on stock return investment decisions of private investors using financial ratio analysis on LQ45 companies. The analysis focuses on the influence of Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM) ratios on stock return.The analysis results indicate that ROA has a positive impact on stock return, as excellent ROA performance reflects management's ability to manage assets to achieve profitability, which can attract investor interest in buying company shares and lead to increased stock return. However, ROE and NPM do not have a positive impact on stock return. Investors tend to consider other financial factors, so even with high ROE and NPM, if other financial indicators show negative performance, company shares may still be perceived poorly by investors.The implications of this research highlight the importance for companies to focus on financial performance, especially ROA, in investment decision-making. Additionally, investors are advised to consider all financial aspects holistically when evaluating the investment potential of stocks.